Wood-based energy in the Northern Forests - Ciolkosz, Daniel (Springer New York Imprint: Springer, 2013)
This unique book provides the first comprehensive overview of wood based bioenergy in the northern hardwood forests of the Eastern United States. This includes a holistic look at the topic of wood based bioenergy, as well as focused analyses of key topics. This book is relevant to engineers, project developers, foresters, economists, sociologists, environmental scientists and natural resource managers. Most chapters also provide practical hands-on advice for the practitioner, and provide a valuable resource for anyone who is considering developing a woody bioenergy project. This book also: Addresses key aspects of the emerging bioenergy economy Covers critical facets of wood based bioenergy projects including environmental, economic, and technological implications and requirements Discusses the various types of wood based bioenergy and how they can be implemented effectively Editors: Michael Jacobson is an Extension Specialist and Professor for the Penn State Department of Ecosystem Science and Management. His degrees are from the University of Connecticut, Duke, and North Carolina State. His academic interests are; forest management; forest economics, finance, policy, and taxes; bioenergy; and international forestry. Daniel Ciolkosz is an Extension Associate for the Penn State Department of Agricultural and Biological Engineering, with degrees from Penn State and Cornell universities. He works extensively with bioenergy systems and businesses, focusing on community and industry education, as well as thermochemical conversion and biomass densification.